2022
DOI: 10.3389/fgene.2022.867231
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Study Reveals New Loci Associated With Pyrethroid Resistance in Aedes aegypti

Abstract: Genome-wide association studies (GWAS) use genetic polymorphism across the genomes of individuals with distinct characteristics to identify genotype-phenotype associations. In mosquitoes, complex traits such as vector competence and insecticide resistance could benefit from GWAS. We used the Aedes aegypti 50k SNP chip to genotype populations with different levels of pyrethroid resistance from Northern Brazil. Pyrethroids are widely used worldwide to control mosquitoes and agricultural pests, and their intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…If our hypothesis is correct, the frequency of the haplotype bearing these resistance mutations may continue to increase in the coming years under continuing selective pressure from insecticide use. Indeed, the Brazilian sample is from 2012, so allele frequencies at these loci may be very different in the present day, as the resistant alleles at V1016I and F1534C are common (Linss et al 2014, David et al 2018, Melo Costa et al 2020, Cosme et al 2022) and increasing in frequency (Linss et al 2014) in some parts of Brazil. This situation highlights the need for an increased use of temporal data in vector genomics.…”
Section: Discussionmentioning
confidence: 99%
“…If our hypothesis is correct, the frequency of the haplotype bearing these resistance mutations may continue to increase in the coming years under continuing selective pressure from insecticide use. Indeed, the Brazilian sample is from 2012, so allele frequencies at these loci may be very different in the present day, as the resistant alleles at V1016I and F1534C are common (Linss et al 2014, David et al 2018, Melo Costa et al 2020, Cosme et al 2022) and increasing in frequency (Linss et al 2014) in some parts of Brazil. This situation highlights the need for an increased use of temporal data in vector genomics.…”
Section: Discussionmentioning
confidence: 99%
“…In Ae. aegypti , variation in ankyrin domain-containing genes has been associated with pyrethroid resistance ( Campbell et al 2019 ); in addition, the ankyrin repeat region-containing gene AAEL011338 was identified as harboring a locus associated with pyrethroid resistance in a Brazilian sample ( Cosme et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…If our hypothesis is correct, the frequency of the haplotype bearing these resistance mutations may continue to increase in the coming years under continuing selective pressure from insecticide use. Indeed, the Brazilian sample is from 2012, so allele frequencies at these loci may be very different in the present day, as the resistant alleles at V1016I and F1534C are common ( Linss et al 2014 ; David et al 2018 ; Melo Costa et al 2020 ; Cosme et al 2022 ) and increasing in frequency ( Linss et al 2014 ) in some parts of Brazil. This situation highlights the need for an increased use of temporal data in vector genomics.…”
Section: Discussionmentioning
confidence: 99%
“…, Ir8) (29), the para sodium channel gene ( e.g. , kdr mutations) (23,30,31), and odorant receptors ( e.g. , AeOR4) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Most efforts have been focused on identifying specific genes linked to hallmarks of domestication such as host-seeking behavior or insecticide resistance, the latter being a side effect of recurrent insecticidal interventions to control mosquito populations (22)(23)(24), based on the differential expression across Ae. aegypti populations (25)(26)(27)(28) and/or the presence of nonsynonymous variants within a few target loci, including genes encoding for detoxification enzymes (e.g., P450s) (23), neurotransmitter receptors (e.g., Ir8) (29), the para sodium channel gene (e.g., kdr mutations) (23,30,31), and odorant receptors (e.g., AeOR4) (6).…”
Section: Introductionmentioning
confidence: 99%